The United States and Cultural Heritage Protection in Japan (1945-1952) - Azimi, Nassrine (Asian history., 2019)
One of the untold stories of the American military occupation of Japan, from 1945 to 1952, is that of efforts by the Arts and Monuments Division of the Supreme Commander for the Allied Powers (SCAP), for the preservation of Japan's cultural heritage. While the role of Allies after WWII in salvaging the cultural heritage of Europe has recently become better known, not much is written of the extraordinary vision, planning and endeavors by curators and art specialists embedded in the US military and later based in Tokyo, and their peers and political masters back in Washington D.C. -- all of whom ensured that defeated Japan's cultural heritage was protected in the chaos and misery of post-war years.